National experience with living donor liver transplantation for hepatocellular carcinoma. Issue 7 (16th April 2022) - Silverstein, Jordyn; Yao, Francis Y.; Grab, Joshua D.; Braun, Hillary J.; Roberts, John; Dodge, Jennifer L.; Mehta, Neil
Abstract: Living donor liver transplantation (LDLT) is an attractive option to decrease waitlist dropout, particularly for patients with hepatocellular carcinoma (HCC) who face lengthening waiting times. Using the United Network for Organ Sharing (UNOS) national database, trends in LDLT utilization for patients with HCC were evaluated, and post‐LT outcomes for LDLT versus deceased donor liver transplantation (DDLT) were compared. From 1998 to 2018, LT was performed in 20, 161 patients with HCC including 726 (3.6%) who received LDLT. The highest LDLT utilization was prior to the 2002 HCC Model for End‐Stage Liver Disease (MELD) exception policy (17.5%) and dropped thereafter (3.1%) with a slight increase following the 6‐month wait policy in 2015 (3.8%). LDLT was more common in patients from long‐wait UNOS regions with blood type O, in those with larger total tumor diameter (2.3 vs. 2.1 cm, p = 0.02), and higher alpha‐fetoprotein at LT (11.5 vs. 9.0 ng/ml, p = 0.04). The 5‐year post‐LT survival (LDLT 77% vs. DDLT 75%), graft survival (72% vs. 72%), and HCC recurrence (11% vs. 13%) were similar between groups (all p > 0.20). In conclusion, LDLT utilization for HCC has remained low since 2002 with only a slight increase after the 6‐month wait policy introduction in 2015. Given the excellent post‐LT survival, LDLT appears to be an underutilized but valuable option for patients with HCC, especially those at high risk for waitlist dropout.